2015
DOI: 10.11114/jets.v4i1.561
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Academic Motivation, Academic Self-efficacy and Attitudes toward Teaching in Pre-service Early Childhood Education Teachers

Abstract: This study is designed to explore academic motivation, academic self-efficacy and attitudes toward teaching in pre-service early childhood education teachers and to investigate the relationships among those variables. Data were gathered through questionnaires administered to 251 pre-service early childhood education teachers. Results indicated that academic motivation was significantly related to academic self efficacy. Although participants had high levels of positive attitudes toward teaching, those attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
(35 reference statements)
1
15
0
4
Order By: Relevance
“…Bandura (2001) and Aydın (2015) claim that high perceived ASEF affects ACM considerably and positively. Similarly, Dogan (2015) and Bedel (2015) state that high perceived ASEF predicts ACM significantly and positively. Khalaila (2015) revealed that perceiving oneself academically self-efficacious improves an individual's intrinsic motivation.…”
Section: Asefmentioning
confidence: 97%
See 1 more Smart Citation
“…Bandura (2001) and Aydın (2015) claim that high perceived ASEF affects ACM considerably and positively. Similarly, Dogan (2015) and Bedel (2015) state that high perceived ASEF predicts ACM significantly and positively. Khalaila (2015) revealed that perceiving oneself academically self-efficacious improves an individual's intrinsic motivation.…”
Section: Asefmentioning
confidence: 97%
“…Similarly, Doğan (2015) revealed in the study with 578 secondary school students that students with high SEF perception levels managed to keep their ACM levels as well, showing the effect of ASEF perception on ACM. In the study with 251 pre-school teachers, Bedel (2015) investigated the relation among ASEF, ACM and attitude towards teaching profession and found that ASEF was a significant predictor of ACM. Yusuf (2011), who studied ASEF and ACM together with learning strategies and academic achievement, also revealed that ASEF perception had a mediator role between ACM and learning strategies, underlying the relation between ASEF and ACM.…”
Section: Hypothesismentioning
confidence: 99%
“…The literature includes a great volume of research on psychosocial domains and self-efficacy (Alemdag & et al 2016a;Alemdag, S. & et al 2016;Ozkara & et al 2016;Alemdag, C. & et al 2016b). Previous research has demonstrated that higher and lower levels of social self-efficacy are associated with shyness, depression instrumentality, expressiveness (Hermann & Betz, 2004), emotional well-being (Bandura et al 1996;Fabio, 2008), loneliness, social dissatisfaction (Galanaki & Kalantzi, 1999), anxiety (Al-Darmaki, 2004;Xu, x.,et al 2017), motivation (Bedel, 2016;Aydın, 2016) and stress (Matsushima & Shiomi, 2003;Moeini, 2008). As social values constantly change and evolve, individuals feel constant concern about their economic status, academic achievements and social relations.…”
Section: Introductionmentioning
confidence: 99%
“…Benzer şekilde, Turgut (2013), lisans öğrencilerinin akademik öz-yeterlik inançları ile akademik performans ve sınıf düzeyleri arasında orta düzeyde bir ilişki olduğunu tespit etmiştir. Yine Bedel (2016) araştırmasında, öğretmen adaylarının akademik öz-yeterlikleri ile akademik motivasyonları arasında anlamlı bir ilişki saptamıştır. Bu araştırmaya göre akademik güdülenme özelliği yükseldikçe akademik öz-yeterlik özelliği de yükselmektedir.…”
Section: Discussionunclassified